Curriculum for neurogastroenterology and motility training: A report from the joint ANMS‐ESNM task force. Issue 9 (25th March 2018) - Gyawali, C. P.; Savarino, E.; Lazarescu, A.; Bor, S.; Patel, A.; Dickman, R.; Pressman, A.; Drewes, A. M.; Rosen, J.; Drug, V.; Saps, M.; Novais, L.; et al.
Abstract: Although neurogastroenterology and motility (NGM) disorders are some of the most frequent disorders encountered by practicing gastroenterologists, a structured competency‐based training curriculum developed by NGM experts is lacking. The American Neurogastroenterology and Motility Society (ANMS) and the European Society of Neurogastroenterology and Motility (ESNM) jointly evaluated the components of NGM training in North America and Europe. Eleven training domains were identified within NGM, consisting of functional gastrointestinal disorders, visceral hypersensitivity and pain pathways, motor disorders within anatomic areas (esophagus, stomach, small bowel and colon, anorectum), mucosal disorders (gastro‐esophageal reflux disease, other mucosal disorders), consequences of systemic disease, consequences of therapy (surgery, endoscopic intervention, medications, other therapy), and transition of pediatric patients into adult practice. A 3‐tiered training curriculum covering these domains is proposed here and endorsed by all NGM societies. Tier 1 NGM knowledge and training is expected of all gastroenterology trainees and practicing gastroenterologists. Tier 2 knowledge and training is appropriate for trainees who anticipate NGM disorder management and NGM function test interpretation being an important part of their careers, which may require competency assessment and credentialing of test interpretation skills. Tier 3 knowledge and training is undertaken by trainees interested in a dedicated NGM career and may be restricted to specific domains within the broad NGM field. The joint ANMS and ESNM task force anticipates that the NGM curriculum will streamline NGM training in North America and Europe and will lead to better identification of centers of excellence where Tier 2 and Tier 3 training can be accomplished. Abstract : The American Neurogastroenterology and Motility Society (ANMS) and the European Society of Neurogastroenterology and Motility (ESNM) jointly evaluated components of NGM training in North America and Europe. A 3 tiered training curriculum covering eleven curriculum domains is proposed and endorsed by all NGM societies. This figure describes a proposed structure of the 3 tiered training.